THE GULLY FORMATION PROCESSES OF THE BASINS AND THEIR IMPLICATIONS ON THE SLOPES STABILITY, A RELIEF EVOLUTION MODEL ON THE BRAZILIAN SAVANNA DOMAIN - Claudete Ap. Dallevedove Baccaro; Ângela Maria Soares (Sociedade & Natureza)
This article brings on the results of specific studies over erosion carried out for twenty years by a crew of researchers of Universidade Federal de Uberlândia. The researches at all took place in Uberlândia, Monte Carmelo, Iraí de Minas counties and others, prior focusing the basins of Douradinho at Uberlândia, Pantaninho and Divisa at Iraí de Minas and Boa Vista at Prata.This Triângulo Mineiro specific area has been through several geographical changes over the twentieth century implying alteration on its landscape structure. According to this, the need of knowing the processes dynamic as well as the diagnoses methods and also how toelaborate bating corrections and means to recover degraded areas has become extremely necessary. The main goal was the identification of either the mechanisms or the conditions stablishers responsible for erosion processes.“The tropical environment is characterized by a damaged landscape composed by potentially affected areas and others recently occupied which present initial effects. Both the areas need planning research. Whenever those environments get altered by human action, their fragilities show up” (Baccaro, 1994:19).